Pathogenic Mechanism of Der p 38 as a Novel Allergen Homologous to RipA and RipB Proteins in Atopic Dermatitis - Jeon, Hyang; Kim, Geunyeong; Kashif, Ayesha; Hong, Min Hwa; Lee, Ji-Sook; Hong, Yujin; Park, Beom Seok; Yang, Eun Ju; Kim, In Sik (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) is a chronic relapsing pruritic disease encompassing skin inflammation and barrier dysfunction. House dust mites are key allergens that augment the development of atopic dermatitis. We aimed to investigate the pathogenic mechanism of AD due to Der p 38, recently identified by us. The frequency of IgE reactivity to Der p 38 in AD subjects was 52.6% (10/19) in a skin prick test and 57.9% (11/19) in a dot blot assay. In human keratinocyte HaCaT cells, Der p 38 triggered the impairment of filaggrin expression and induced pro-inflammatory cytokines such as IL-6, IL-8 and MCP-1 through TLR4, PI3K, AKT, JNK and NF-κB pathway. Supernatants from Der p 38-treated cells blocked filaggrin expression and neutrophil apoptosis. The anti-apoptotic effect of the Der p 38-released molecules on neutrophils was accomplished by inhibition of the caspase 9/3 pathway, and by increased MCL-1 expression and BCL2/BAX expression ratio. In C57BL/6 wild type (WT) mice, Der p 38 induces a dose-dependent increase of AD-like skin lesions, with enhanced expressions of total and Der p 38-specific IgE. Der p 38 also diminished the expressions of skin barrier proteins and induced JNK activation. However, the AD-like features following cutaneous Der p 38 exposure were observed to be reduced in the TLR4 knockout (KO) group, as compared to the WT group. Skin infiltration of neutrophils, eosinophils and mast cells was increased in the WT mice, but was not portrayed in the TLR KO mice. These findings indicate that Der p 38 is a novel mite allergen that triggers AD by lowering skin barrier proteins and increasing inflammatory cells. Results of this study have thereby paved the way to unveil the pathogenic mechanisms of AD.